2007
DOI: 10.1111/j.1540-8191.2007.00382.x
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic Dysfunction After Coronary Artery Bypass Grafting?The Effect of Glucose-Insulin-Potassium Infusion

Abstract: The study was partially supported by Agilent Technologies/Philips Imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…1,2,4, 10 The hyperglycemia can have 2 main causes. 3,4 It has been demonstrated that hyperglycemia accompanies ACSs, 10 and that this is a negative predictive factor for cardiovascular risk. Hyperglycemias found in patients with low (Ͻ5 UI/mL) insulin levels should have another explanation such as pancreatic incapacity to secrete insulin due to hypoperfusion, thus compromising basal state.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,4, 10 The hyperglycemia can have 2 main causes. 3,4 It has been demonstrated that hyperglycemia accompanies ACSs, 10 and that this is a negative predictive factor for cardiovascular risk. Hyperglycemias found in patients with low (Ͻ5 UI/mL) insulin levels should have another explanation such as pancreatic incapacity to secrete insulin due to hypoperfusion, thus compromising basal state.…”
Section: Discussionmentioning
confidence: 99%
“…На данный момент не выделено специфической фармакотерапии, влияющей на исход. Существуют общие подходы в интраоперационный период, например, ограничение волемической нагрузки при повышении давления наполнения или сохранение нормального ритма/ограничения тахикардии при нарушенной релаксации [28][29][30].…”
Section: ведение пациентов с дд интраоперационноunclassified
“…© 2020 Forum Multimedia Publishing, LLC Barcellos 2007;Ellenberger 2018;Foroughi 2012;Howell 2011;Koskenkari 2005;Koskenkari 2006;Lazar 2004;Licker 2019;Ranasinghe 2006;Roh 2015;Rujirojindakul 2014;Seied-Hosseini 2010;Smith 2002;Straus 2013;Tsang 2007;Visser 2005]. Figure 1 shows the details of the study selection process in the meta-analysis (Figure 1).…”
Section: E65mentioning
confidence: 99%